Governos locais e políticas de promoção econômica: uma análise da promoção econômica nos municípios brasileiros com população acima de 50 mil habitantes - Camara, Richardson Leonardi Moura da (2014)
This work aims to analyze the policy of economic promotion in the Brazilian cities of medium and great size (with population above of 50.000 hab.). The objective of the research is to launch light in the debate on the regional and municipal development, presenting the recent hypotheses supplied by literature. Of complementary form, had for specific objective presents the results of the Research of Basic Information of Cities - PIM, of Brazilian Institute of Geography and Statistics (IBGE), in two surveys carried through together to the Brazilian local governments (1999 and 2009). It analyzes the instruments of economic promotion used by local governments and the influence of the development variables, as the Local Human Index of Development (HID-L) and the Local Gross Domestic Product (GDP-L). The research sample that factors as HID-L and GDP-L has significant influence in economic promotion of cities and must be taken in account in the definition of the local strategies of development